Pengaruh Proses Pengeringan Terhadap Kadar Total Fenolik Dan Flavonoid Ekstrak Metanol Kubis Ungu(BrassicaoleraceaeL) - Armon Fernando; Azkia Wanudya Rahmadhani; Emma Susanti (LPPM Universitas Dharma Andalas, 2023)
Purplecabbage(BrassicaoleraceaeL.)isoneoftheagriculturalproductsinIndonesiawhoseexistenceisstartingtobequitewellknownbythepublic.Purple cabbage contains secondary metabolites that are thought to have antioxidant activity, the name is flavonoids and phenolics. This study aims toexamine the effect of the drying process of purple cabbage extract on total phenolic and flavonoid using 3 drying methods, wind drying, light bulb andoven.Thetestresultsshowedthatthemethanolextractofpurplecabbageonwinddryinghadthehighesttotalphenolicandflavonoidcontentobtainedin the methanol extract of the wind drying method, then the methanol extract of oven drying and drying using a light bulb. Of the 3 methods of dryingpurplecabbagemethanolextract,itdidnothavea significanteffect (p>0.05)on thetotalphenolicand flavonoidcontent.